2009
DOI: 10.1001/archinternmed.2008.564
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Physician Reminders to Promote Colorectal Cancer Screening

Abstract: Background Screening reduces colorectal cancer mortality, but effective screening tests remain underused. Systematic reminders to patients and physicians could increase screening rates. Methods We conducted a randomized controlled trial of patient and physician reminders in 11 ambulatory health centers. Participants included 21,860 patients ages 50 to 80 overdue for colorectal cancer screening and 110 primary care physicians. Patients were randomly assigned to receive mailings containing an educational pamph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
187
4
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(200 citation statements)
references
References 68 publications
7
187
4
2
Order By: Relevance
“…Numerous strategies exist to improve screening rates for colorectal and breast cancer, 2,3,5,6,[11][12][13][14][15][16][17][18][19][20] but the relative incremental benefit of these interventions have not been compared. 5 Using a pragmatic randomized trial, we examined the incremental benefit of several strategies to augment the effect of a patient reminder letter to improve cancer-screening rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous strategies exist to improve screening rates for colorectal and breast cancer, 2,3,5,6,[11][12][13][14][15][16][17][18][19][20] but the relative incremental benefit of these interventions have not been compared. 5 Using a pragmatic randomized trial, we examined the incremental benefit of several strategies to augment the effect of a patient reminder letter to improve cancer-screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support those of previous studies. 11,[22][23][24] Green et al recently found that an automated mailing led to twice as many persons being screened for colorectal cancers. 23 Adding navigated interventions, such as guided support from a registered nurse, led to further improvements in CRC screening rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions targeting physicians have included academic detailing, 26,27 chart audit and feedback, 28,29 reminder systems, 30 and communication skills training. 21,29 Pre-visit patient-level interventions in patients of lower socioeconomic status, which have been effective in increasing CRC screening discussions/recommendations, include activation counseling, 31,32 computer-delivered tailored intervention 33 and decision aids.…”
Section: Discussionmentioning
confidence: 99%